Trimester report. - Indiana University. Archives of Traditional Music (Bloomington., 1964)
Principally "Recent accessions of sound recordings."
Keywords: Indiana University. -- Archives of Traditional Music; Folk music -- Discography -- Catalogs -- Periodicals; Folk songs -- Discography -- Catalogs -- Periodicals